Exploring the relationship between motivation and science achievement of secondary students - Leong, Kwan Eu; Tan, Pei Pei; Lau, Poh Li; Yong, Sook Lu (Universiti Putra Malaysia, 2018)
Motivation plays an important role in students' learning and academic performance. It is believed that intrinsic and extrinsic motivation contributes in the learning process in different ways. This study examined the effects of intrinsic and extrinsic motivation on student science achievement using the Trends in Mathematics and Science Study (TIMSS) 2011 data. Furthermore, the study explored how intrinsic and extrinsic types of motivation function across different cultures. The sample consisted of eighth grade students from the United States, England, Malaysia, and Singapore. Students from the Western culture value extrinsic motivation higher than intrinsic motivation in science learning. The findings also showed that students with high intrinsic motivation perform better than students with low intrinsic motivation across the four countries. Positive relationship between motivation and science achievement supported motivation theory in which higher motivation led to higher achievement scores. Students with intrinsic motivation obtain higher score in science compared to extrinsically motivated students. This study also showed cultural differences affect students' types of motivation. Furthermore, this study could be practically valuable in providing insight on understanding the motivation levels in enhancing students' science achievement.